2016
DOI: 10.1089/ten.teb.2015.0290
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Derived Extracellular Matrix: Basic Characteristics and Current Applications in Orthopedic Tissue Engineering

Abstract: The extracellular matrix (ECM) is a dynamic and intricate microenvironment with excellent biophysical, biomechanical, and biochemical properties, which can directly or indirectly regulate cell proliferation, adhesion, migration, and differentiation, as well as plays key roles in homeostasis and regeneration of tissues and organs. The ECM has attracted a great deal of attention with the rapid development of tissue engineering in the field of regenerative medicine. Tissue-derived ECM scaffolds (also referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 92 publications
1
74
0
Order By: Relevance
“…Tracking of the donor cell fate confirmed the sustained donor cell survival and differentiation over 7-week period in vivo in the layer-by-layer assembled 3D scaffolds. The beneficial effects of the native ECM in bone/cartilage engineering have been extensively published [41, 42]. Our current study demonstrated a simple strategy to optimize the performance of electrospun nanofibrous sheets in bone repair and bone tissue engineering.…”
Section: Discussionmentioning
confidence: 77%
“…Tracking of the donor cell fate confirmed the sustained donor cell survival and differentiation over 7-week period in vivo in the layer-by-layer assembled 3D scaffolds. The beneficial effects of the native ECM in bone/cartilage engineering have been extensively published [41, 42]. Our current study demonstrated a simple strategy to optimize the performance of electrospun nanofibrous sheets in bone repair and bone tissue engineering.…”
Section: Discussionmentioning
confidence: 77%
“…Cultured cell-derived ECM has been used as an alternative to tissuederived ECM (Zhang et al, 2016). In fact, ECM proteins can be secreted by cells cultured in vitro and then decellularized to create the cellderived ECM (Hoshiba, Cho, Murakawa, Okahata, & Akaike, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although both Matrigel and chondrocyte derived extracellular matrix are used to promote cell proliferation, the former is known for its gel composition at room temperature containing bFGF, IGF, EGF, laminin, collagen 1, and heparin sulfate proteoglycan [12], which exerts a slow release characteristic that favors angiogenesis [1316]. In the mice model injected with Matrigel reported by Cox, there was no tissue growth at day 6.…”
Section: Discussionmentioning
confidence: 99%